2015
DOI: 10.1007/s10490-015-9413-4
|View full text |Cite
|
Sign up to set email alerts
|

Collective efficacy as a mediator between cooperative group norms and group positive affect and team creativity

Abstract: In spite of a growing body of research on creativity in team contexts, very few researchers have paid attention to the team-level antecedents and mediating processes of team creativity. To fill this gap, drawing on social cognitive theory and Dzindolet's group creativity process model, this study examined cooperative group norms and group positive affect as antecedents of team creativity and explored collective efficacy as an intermediary mechanism between these relationships. The current study was conducted w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 98 publications
(161 reference statements)
3
67
1
1
Order By: Relevance
“…positive affect and creativity at the team level (Shin, 2014). In line with this stream of research, although very little, prior work has identified collective efficacy (Kim & Shin, 2015), team promotion focus, and team reflexivity (Shin, 2014) as mediators of the PGAT-team creativity relationship. Replicating Shin's (2014) findings, our study demonstrated that team reflexivity was a key intermediary process underlying the relationships between PGAT and team creative performance and change OCB.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…positive affect and creativity at the team level (Shin, 2014). In line with this stream of research, although very little, prior work has identified collective efficacy (Kim & Shin, 2015), team promotion focus, and team reflexivity (Shin, 2014) as mediators of the PGAT-team creativity relationship. Replicating Shin's (2014) findings, our study demonstrated that team reflexivity was a key intermediary process underlying the relationships between PGAT and team creative performance and change OCB.…”
Section: Discussionmentioning
confidence: 96%
“…Given that future‐oriented, improvement‐related actions are becoming increasingly important to organizational effectiveness (Choi, ), our study aims at unveiling the crucial antecedent and mechanism leading to the creative performance and change OCB of work teams. Drawing on the literature on affect, creativity, and OCB (e.g., George, ; Kim & Shin, ; Rhee, ; Shin, ; Tsai, Chi, Grandey, & Fung, ), we isolate positive group affective tone (PGAT) as a primary antecedent of team creative performance and team change OCB. Although scant prior research has identified collective efficacy (e.g., Kim & Shin, ), team reflexivity, and team promotion focus (e.g., Shin, ) as critical mediating mechanisms underlying the relationship between PGAT and team creativity.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive affect has been identified as a probable antecedent to creativity (Baas, De Dreu, & Nijstad, 2008;Kim & Shin, 2015). Clore, Schwarz, and Conway (1994) suggested that creativity may be fostered when some cognitive variations occur due to the experience of positive affect.…”
Section: Positive Affect and Creativitymentioning
confidence: 99%
“…Overall, the group creativity model suggests a theoretical framework that explains how input variables (e.g., group norms, organizational structure and goals, diversity and cohesiveness of group, and group members' personalities and abilities) affect group-level creativity. This frame emphasizes the important role of various intermediating processes (i.e., cognitive, motivational, and social processes) between input factors and creativity [16,17]. Because CSR activities could be interpreted as both critical group norms and an organizational goal, CSR can be an important input factor.…”
Section: Introductionmentioning
confidence: 99%